In Arabidopsis thaliana Cadmium Impact on the Growth of Primary Root by Altering SCR Expression and Auxin-Cytokinin Cross-Talk - Bruno, Leonardo; Pacenza, Marianna; Forgione, Ivano; Lamerton, Liam R.; Greco, Maria; Chiappetta, Adriana; Bitonti, Maria B. (Frontiers in Plant Science, 2017)
Cd is one of the most widespread pollutants in both terrestrial and marine environment, and its inhibitory effect on plant growth has been largely demonstrated. However, the molecular mechanisms underlying Cd toxicity in plant and mainly in the root, as the first organ sensing soil heavy metals, need to be better investigated. To this aim, in the present work, we analysed the growth and the organization of Arabidopsis thaliana primary root in seedlings exposed to Cd (25 and 50 µM) for 8 days starting from germination. Root length, root meristem size and organization were evaluated together with the behaviour of some of the major molecular players in root growth and patterning. In particular, by using different GFP transgenic lines, we monitored: i) the expression pattern of WOX5 and SCR transcription factors involved in the establishment and maintenance of stem cell niche and in the control of meristem size; ii) the expression pattern of the IAA-inducible pDR5::GFP reporter, PIN 1, 2, 3, 7 auxin carriers, and TCSn::GFP cytokinin-sensitive sensor as relevant components of hormone circuit controlling root growth. We report that Cd exposure inhibits primary root growth via affecting RAM stem cell niche and root radial pattern. At the molecular level, an impairment of auxin maximum accumulation at the root tip, related to a down-regulation and mislocalisation of PIN proteins, and an enhancement of TCSn::GFP cytokinin–sensitive sensor signal is also detected under Cd treatment, thus suggesting an alteration in the homeostasis of auxin/cytokinin signaling. Moreover, and for the first time, Cd toxicity on root growth and pattern has been related to a misexpression of SCR transcription factors which are known to interplay with auxin/cytokinin cross-talk in the control of RAM maintenance and activity.